Lateral Approach Sinus (LAS) and Crestal Approach Sinus (CAS): The Unravelled Paraphernalia for Maxillary Sinus Membrane Advancement (Global Journal of Medical Research, 2023)
The permanent replacement of missing teeth in the maxillary posterior tooth region becomes a tedious task when it is confounded with bone atrophies To overcome this problem and achieve successful rehabilitation maxillary sinus membrane elevation procedures have been advocated as the most reliable means The lateral window technique and the crestal approach are two of the most common approaches These technologically developed procedures have reported high success rates in cases of deficient residual bone Over time there have been many advancements in these techniques that led to the development of user-friendly kits like the Lateral approach Sinus LAS kit and the Crestal approach Sinus CAS kit In this case series we have reported two cases treated with either of these approaches and have compared the same
Keywords: crestal approach sinus lift; hard tissue augmentation; lateral window approach sinus lift